The Potential of Guanidino Acetic Acid to Reduce the Occurrence and Severity of Broiler Muscle Myopathies - Oviedo-Rondón, Edgar Orlando; Córdova-Noboa, Hernan Alejandro (Frontiers in Physiology, 2020)
Guanidinoacetic acid (GAA) is the biochemical precursor of creatine, which, in its phosphorylated form, is an essential high-energy carrier in the muscle. While creatine has limited stability in feed processing, GAA is well established as a source of creatine in the animal feed industry. Published data have demonstrated beneficial effects of GAA supplementation on muscle creatine, energy compounds, and antioxidant status leading to improvements in broiler body weight gain, FCR, and breast meat yield. Although increases in weight gain and meat yield are often associated with wooden breast (WB) and other myopathies, recent reports have suggested the potential of GAA supplementation to reduce the occurrence and severity of WB, while improving breast meat yield. This disorder increases the hardness of the Pectoralis major muscle and has emerged as a current challenge to the broiler industry worldwide by impacting meat quality. Genetic selection, fast-growth rates, and environmental stressors have been identified to be the main factors related to this myopathy, but the actual cause of this disorder is still unknown. Creatine supplementation has been used as a nutritional prescription in the treatment of several muscular myopathies in humans and other animals. Since GAA is a common feed additive in poultry production, the potential of GAA supplementation to reduce broiler myopathies has been investigated in experimental and commercial scenarios. Besides, a few studies have evaluated the potential of creatine in plasma and blood enzymes related to creatine to be used as potential markers for WB. The evidence indicates that GAA could potentially minimize the incidence of WB. More data are warranted to understand the factors affecting the potential efficacy of GAA to reduce the occurrence and severity of myopathies.